#Covid-19: An exploratory investigation of hashtag usage on Twitter. Issue 4 (April 2021) - Petersen, Kai; Gerken, Jan M.
Highlights: We investigated 6.9 million tweets on Covid-19 and analyzed their hashtags. 13 themes of interest were identified concerning hashtags. Health-policy makers can use the hashtags to search and communicate. We encourage a stronger presence of health-policy makers on Twitter. Abstract: Background: The literature highlights Twitter as a vital instrument tool for health policy-makers for health communication and promotion. Furthermore, Twitter is a tool allowing us to understand the focus of people regarding a topic of interest. Objective: To provide health policy-makers with insights concerning key topics of interest in the Twitter community regarding Covid-19, and to support information search and health communication. Method: A total of 28.5M tweets have been retrieved, of which 6.9M tweets included hashtags. The data was analyzed using data science and natural language processing libraries. Qualitative analysis was performed using thematic analysis. Results: 907k different hashtags were used. Of these, only 1192 hashtags were used more than 1000 times. The qualitative analysis resulted in 13 themes. The top three themes regarding the number of hashtags used were related to Covid-19, identifying information, interventions, and geographical tagging. We explored the relationship between themes and showed how health practitioners can understand the communication in relation to specific topics expressed as hashtags (e.g., #stayhome). Conclusions: The results provide first insights for policy-makers and health practitioners to identify relevant tweets and to choose appropriate hashtags for health communication. The results also show that only with a limited number of Tweets (10 per day) health organizations could have been among the top users.